2017
DOI: 10.1002/aur.1798
|View full text |Cite
|
Sign up to set email alerts
|

Placebo‐like response in absence of treatment in children with Autism

Abstract: Caregiver report is the most common measure of change in pediatric psychiatry. Yet, placebo response rates pose significant challenges to reliably detect a treatment response. The present study simulated an eight-week clinical trial protocol for Autism Spectrum Disorder (ASD) for the purpose of testing the feasibility and validity of several outcome measures. Twenty caregivers answered questions about their child's behavior on their smartphone each week and completed a battery of paper questionnaires during we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…Many systems used for tracking treatment outcomes are based on parent report via interviews or questionnaires or expert clinical assessment. However, recent research has highlighted the presence of a striking placebo effect in ASD populations: even when outcome evaluators are masked to treatment condition, significant improvements are still reported in a surprisingly substantial number of participants assigned to control conditions [Bradshaw et al, ; Jones, Carberry, Hamo, & Lord, ; Masi, Lampit, Glozier, Hickie, & Guastella, ]. This, in addition to the cost of training and maintaining fidelity on clinically based measures, leads us to believe that neither questionnaires nor clinical phenotyping are optimal outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Many systems used for tracking treatment outcomes are based on parent report via interviews or questionnaires or expert clinical assessment. However, recent research has highlighted the presence of a striking placebo effect in ASD populations: even when outcome evaluators are masked to treatment condition, significant improvements are still reported in a surprisingly substantial number of participants assigned to control conditions [Bradshaw et al, ; Jones, Carberry, Hamo, & Lord, ; Masi, Lampit, Glozier, Hickie, & Guastella, ]. This, in addition to the cost of training and maintaining fidelity on clinically based measures, leads us to believe that neither questionnaires nor clinical phenotyping are optimal outcome measures.…”
Section: Introductionmentioning
confidence: 99%
“…Language difficulties are a hallmark of neurodevelopmental disorders with the majority of behavioral interventions targeting spoken language [Abbeduto, McDuffie, Thurman, & Kover, 2016]. Changes in social communication are commonly assessed through caregiver or clinician report [Budimirovic et al, 2017;McConachie et al, 2015], yet these measurements can be biased by expectations [Guastella et al, 2015;Jones, Carberry, Hamo, & Lord, 2017;Jones et al, 2015;King et al, 2013;Jones, Tarpey, Hamo, Carberry, & Lord, 2018], warranting the need for objective, direct measures from the child. Speech from the child is typically assessed through human, manual transcriptions [Berry-Kravis et al, 2013;Sheinkopf, Mundy, Oller, & Steffens, 2000]; however, these procedures are costly and time intensive.…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings from a simulated 8-week clinical trial protocol for ASD [Jones, Carberry, Hamo, & Lord, 2017] showed placebo-like (positive) responses in caregiver ratings even in absence of treatment, while no significant changes in clinical ratings of ASD symptoms were noted.…”
Section: Discussionmentioning
confidence: 96%
“…Recent findings from a simulated 8‐week clinical trial protocol for ASD [Jones, Carberry, Hamo, & Lord, ] showed placebo‐like (positive) responses in caregiver ratings even in absence of treatment, while no significant changes in clinical ratings of ASD symptoms were noted. This study indicates that a placebo‐like effect is less likely to influence independent expert ratings, whereas therapists and caregivers will tend to overestimate intervention effects because they believe in the intervention they administer and in their therapeutic orientation.…”
Section: Discussionmentioning
confidence: 99%